Cultural Diversity and Performance: A Case Study among University Students - Sorooshian, Shahryar; Tolgambayeva, Dinara (AesthetixMS: Aesthetics Media Services, 2016)
This report focuses on the effects of cultural diversity (CD) on team performance among university students and explores the relationship between team performance and CD. It identifies that there is a strong indirect relationship between these two concepts. Therefore, the nature of this relationship was investigated in details. The report identified that there are positive and negative effects of CD on intermediate outcomes of the team. The analysis has been performed to further develop the understanding of the subject of CD and the effects on team performance. The results of the analysis have been discussed in details with providing the required information in the analysis part